Evaluasi Tata Kelola Teknologi Informasi Pada Diskominfosantik Kabupaten Bekasi Menggunakan Kerangka Kerja COBIT 5 Subdomain EDM04 dan APO07 - Muhammad Abdullah Al Munawar; Buce Trias Hanggara; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Communication, Information, Statistics and Encoding Office (Diskominfosantik) of Kabupaten Bekasi is an institute which responsible to manage information and communication for Kabupaten Bekasi region. There are problems regarding the management of IT resources, which is the lack of human resources caused multipled job. Lack of human resource inhibits management of infrastructure and application that are being improve to reach the smart village program. Another trouble is uncompleted standard operating procedure of IT resources management about responsibilities of IT resource and there is no mechanism of IT resource management where all responsible was given to vendor. Evaluation is required to overcome the current problems. Evaluation using COBIT 5 subdomain EDM04 and APO07 is appropriate to evaluate management of IT resource. COBIT 5 is able to detect value of capability level as is and to be and gap analysis. Based on result of this evaluation, capability level EDM04 is in 1st level and APO07 is 2nd level and gap analysis of each subdomain is 1 level. Recommendation given to make SOP for problem deviation, document priority arrangement of IT resource management, giving competency training about management of IT for employee